THE EFFECTIVENESS OF THE ACTIVE LEARNING STRATEGY OF THE FIRING LINE TYPE IS VARIED WITH MEANINGFUL SCRIPT ON RESULTS AND ACTIVITY OF STUDENT LEARNING MATERIALS ON HUMAN REPRODUCTIVE SYSTEM IN CLASS XI IPA SMA PARULIAN 1 MEDAN - Sopan Sopian Panggabean; Hendro Pranoto; Adriana Y.D LumbanGaol (Universitas Negeri Medan, 2017)
This research is aimed at determining the effectiveness of the active learning strategy of The FiringLine type is varied with meaningful script on results and activity of student learning materials on humanreproductive system in class XI IPA SMA Parulian 1 Medan Academic Year 2016/2017. This type of research ispre-experiment, where the population in this study are the students of class XI IPA SMA Parulian 1 Medan with57 students. Sampling was performed by using the random sampling technique. The result show that studentmastery level classified in the category of high with a value of 80, students™ learning completeness classified inthe category of complete with a value of 89.3%, and student learning activities classified in the category ofactive with a value of 77.60. So it can be concluded that the active learning strategy of The Firing Line type isvaried with meaningful script effectively used on the material of the human reproduction system in class XI IPASMA Parulian 1 Medan Academic Year 2016/2017.Key Words : Active Learning Strategy Of The Firing Line Type, meaningful script, activity learning.